Factors Affecting Financial Performance in Banking Companies 2020-2022 - Fa'ida, Maf'ulatul; Tohari, Amin; Puspita, Erna (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim: The aim of this study is (1) to investigate the partial effects of Corporate Social Responsibility, independent commissioners, and Company Size on Financial Performance. (2) to examine the combined effects of independent commissioners, corporate social responsibility, and company size on financial performance. Research Method: This study employs a quantitative approach. The sample consists of 30 companies selected through purposive sampling method. Multiple Linear Regression Analysis Technique is utilized for analysis, employing SPSS software version 23.  Research Findings: The findings reveal that (1) Corporate Social Responsibility and company size individually exert a significant impact on the company's financial performance, whereas independent commissioners show no significant partial effect on financial performance. (2) Corporate social responsibility, independent commissioners, and company size collectively demonstrate a significant effect on the company's financial performance.